How strong is the edge effect in the adsorption of anticancer drugs on a graphene cluster? - Chompoonut Rungnim (2018)
© 2016, Springer-Verlag Berlin Heidelberg. The adsorption of nucleobase-analog anticancer drugs (fluorouracil, thioguanine, and mercaptopurine) on a graphene flake (C54H18) was investigated by shifting the site at which adsorption occurs from one end of the sheet to the other end. The counterpoise-corrected M06-2X/cc-pVDZ binding energies revealed that the binding stability decreases in the sequence thioguanine > mercaptopurine > fluorouracil. We found that adsorption near the middle of the sheet is more favorable than adsorption near the edge due to the edge effect. This edge effect is stronger for the adsorption of thioguanine or mercaptopurine than for fluorouracil adsorption. However, the edge effect reduces the binding energy of the drug to the flake by only a small amount, <5 kcal/mol, depending on the adsorption site and the alignment of the drug at this site.